Factors of the Development and Decline in New Industrial Era: A Case Study of 7-Eleven - Zi Jian Oh; Gai Sin Liem; Safina binti Ismail; Siti Aina Antasya binti Mohd Indera JR; Nur Muslihah binti Abdul Hakim; Ivan Febrianto; Su Wei Sia; Jo Ying Tan; Wei Qi Tan; Hui Wen Ting; Daisy Mui Hung Kee (AIBPM Publisher, 2021)
The purpose of this study is to investigate factors of the development and decline of 7-Eleven in the new industrial era. This study examined the relations between marketing mix strategy (4Ps) and customer satisfaction significantly predicting the development and decline of 7-Eleven. A total of 108 respondents, 56 Malaysian and 52 Indonesian, were involved to collect the data by questionnaires. The regression results provided sufficient evidence that factors of 7-Eleven development are positively related to its marketing mix strategy and customer satisfaction or vice versa. This finding provides profound understanding about the relationship between the development and decline factors in new industrial era, its marketing mix strategy and customer satisfaction.